Generalized relation of bitumen stress at shear to its penetration in a range from softening point temperature to breaking point temperature - Zolotaryov, Victor; Золотарьов, Віктор Олександрович (Харківський національний автомобільно-дорожній університет, 2022)
The problem of assessing the quality of bitumen is in the fact that the common quality indicators are empirical. They do not allow the objective characterization neither the consistency of bitumen no its transition from one state of matter to other. Goal. The solution to this problem is based on the principle that the resistance of bitumen to the penetration of the needle is a shear characteristic under conditions of complete adhesion to the surface of the needle. Methodology. The practical confirmation of this approach is based on the Core & Laurent method, which takes into account the rate of the bitumen layer and the resistance force to this displacement based on the geometric parameters of the needle and the force applied to it. Attempts to estimate bitumen viscosity with the depth of needle penetration have failed for two reasons. Firstly, bitumen viscosity is principally a technological characteristic. Secondly, in the simple conversion of the penetration value into viscosity neither the shear rate nor flow anomalies and a units ratio were taken into account. Results. In this research work the shear stress at penetration at the softening point temperature and breaking point temperature is taken as a mechanical characteristic of the states of matter. This statement of the problem is based on the linearity of the relationship between the test temperature and log of penetration, established by Hekelom. Later, this relationship was supplemented with a temperature of equal penetration T31 as a midpoint of the plasticity interval of bitumen with the same penetration but different penetration indexes. Practical value of this work is results in finding the relation between penetration and the reverse pliability G*/sin φ, which is applied in the Superpave system to evaluate the bitumen component in the rutting resistance of asphalt concrete.
Узагальнений взаємозв’язок напруження зсуву бітуму від його пенетрації в діапазоні від температури розм’якшеності до температури крихкості
Keywords: bitumen; softening point temperature; penetration; isopenetration; breaking point temperature; complex modulus; phase angle; stress; бітум; температура розм’якшеності; пенетрація; ізопенетрація; температура крихкості; комплексний модуль; фазовий кут; напруга; 665.775; 10.30977/BUL.2219-5548.2022.96.0.121